The Shifting Power Structure of Northeast Asia and China’s Strategic Choices in the 2020s - Qi Huaigao; Li Kaisheng (Международная аналитика, 2020)
The Northeast Asian (NEA) power structure demonstrates a weakening unipolarity of the United States (U.S.), which will evolve into a power structure with “multilateral co-opetition of two superpowers (China and the U.S.) and three regional great powers (Russia, Japan, and South Korea)” during the 2020s. In the context of this shifting power structure, the other fi ve NEA states will adjust their diplomatic policies. Japan, Russia, and South Korea, which occupy the second tier of the NEA power structure, will pursue regional great power diplomacy and regional interests. Russia will maintain a careful balance with China and the U.S., and will use investments from the other NEA states pragmatically to develop its Far East region. Japan will seek to maximize its security guarantees from the U.S. while actively obtaining economic benefi ts from China, and will try to remain fl exible in terms of its NEA strategic choice. South Korea will implement the so-called “two superpowers diplomacy” in relation to the U.S. and China in order to enhance its strategic autonomy. With relatively weak national power, North Korea and Mongolia occupy the third tier of the NEA power structure, and they will try to ensure the survival of their respective regimes and promote national security. China’s strategic choices for NEA in the next decade are likely to include fi ve aspects: 1) to avoid a “new Cold War” and achieve a strategic balance with the U.S.; 2) to maintain friendly and close strategic ties with Russia; 3) to actively promote economic cooperation with the other NEA countries; 4) to promote the establishment of a regional security mechanism in the future that includes all the NEA states, for example, a “Northeast Asia Peace and Cooperation Organization” (NEAPCO); and 5) to construct a collective NEA identity.